Microwave dielectric characteristics of (1-x)(Al1/2Ta1/2)O-2-xTiO(2) ceramics - Choi, JW; Yoon, SJ; Kim, HJ; Yoon, KH (INST PURE APPLIED PHYSICS, 2002)
The microwave and structural characteristics of (1 - x)(Al1/2Ta1/2)O-2-xTiO(2) (0 < x < 0.5) ceramics were investigated. (Al12Ta1/2)O-2 and TiO2 had orthorhombic and tetragonal structure. respectively, As TiO2 concentration increased, (1 - x)(Al1/2Ta1/2)O-2-xTiO(2) transformed to tetragonal structure. Specimens having a tetragonal single phase could he obtained for x greater than or equal to 0.15. As TiO2 concentration increased, the grain size. dielectric constant (epsilon(r)) significantly increased, and the temperature coefficient of resonant frequency (tau(f)) changed from negative to positive value. However. quality factor (Q) increased within limited values. A tau(f) of 0 ppm/degreesC was realized at x = 0.2 and the epsilon(r) and Q.f(0) value for this Composition were 29.4 and 75470 GHz, respectively. The relationship between microstructures and dielectric properties was also investigated.
Keywords: RESONATOR